2004
DOI: 10.1111/j.1600-051x.2004.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a chlorhexidine regimen on de novo plaque formation

Abstract: Habitat is critical in controlling the bacterial composition of the dental biofilm. The microbiota will tend to go back to the one that is characteristic of a given subject, once chemical antimicrobial means are withdrawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
1
29
1
6
Order By: Relevance
“…Optimally, mouthrinsing should be performed twice daily. The substantivity of current mouthrinses is of less than 12 hours duration [20] and after four days of not rinsing, it has been shown that bacterial composition of plaque returns to its baseline level before rinsing was initiated [21] Segreto et al, [22], who showed that 15 ml of either 0.12% or 0.2% chlorhexidine mouthwash was significantly clinically better than placebo mouthwash when used alongside toothbrushing. The high efficacy could be explained by its immediate bactericidal action during the time of application followed by a prolonged bacteriostatic action due to adsorption on the tooth surface [23].…”
Section: Discussionmentioning
confidence: 99%
“…Optimally, mouthrinsing should be performed twice daily. The substantivity of current mouthrinses is of less than 12 hours duration [20] and after four days of not rinsing, it has been shown that bacterial composition of plaque returns to its baseline level before rinsing was initiated [21] Segreto et al, [22], who showed that 15 ml of either 0.12% or 0.2% chlorhexidine mouthwash was significantly clinically better than placebo mouthwash when used alongside toothbrushing. The high efficacy could be explained by its immediate bactericidal action during the time of application followed by a prolonged bacteriostatic action due to adsorption on the tooth surface [23].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of chlorhexidine has been defined elsewhere, with activity against gram-positive, gram-negative and some fungi. Further when used as mouthwash at 0.12%, it reduce several species of the bacteria in saliva (12). In the current study, blood cultures results showed that there were no statistically significant difference between patients who used chlorhexidine during hospitalization (GA=23.6%) and patients that did not use chlorhexidine (GB=28.6%).…”
Section: Discussionmentioning
confidence: 65%
“…Por lo tanto, se decidió utilizar el modelo de formación de placa de novo en cuatro días, descrito en la bibliografía (21,22) . El diseño experimental ha sido utilizado por varios autores, entre ellos Sekino (23) , Moran (24) , Arweiler (25) , Herrera (26) , Welk (27) y Witt (28) . La principal variable medida en estos estudios es el índice de Placa y todos los autores mencionados utilizan el índice de Quigley & Hein (1962) modificado por Turesky y cols., a excepción de Arweiler (25) que utiliza el índice de Silness & Löe (1964), por lo tanto, los resultados con respecto al índice de Placa podrían ser comparables.…”
Section: Discussionunclassified
“…Los valores del índice de Placa que obtuvo Moran (24) después del uso de clorhexidina fueron notablemente inferiores, muy distante del valor alcanzado en este estudio. La metodología de Sekino (23,30) difiere de la utilizada en este estudio, ya que los colutorios fueron administrados en los periodos preparatorios y en el periodo de acumulación de placa no había ningún tipo de control de ésta. Shinada y cols., usando un colutorio con polifenoles, encuentra una reducción del índice de Placa un poco mayor, pero sólo en tres días de tratamiento (31) .…”
Section: Discussionunclassified